Molecular mechanisms of epithelial–mesenchymal transition - Lamouille, Samy; Xu, Jian; Derynck, Rik (Nature reviews. Molecular cell biology, 2014)
Key Points The epithelial–mesenchymal transition (EMT) process results in the downregulation of epithelial, and activation of mesenchymal, cell characteristics and behaviour. This transdifferentiation process is initially reversible, with mesenchymal–epithelial transition (MET) enabling reversion to an epithelial phenotype. Both epithelial and endothelial cells can transition into a mesenchymal phenotype. EMT is integral in development, starting with the generation of mesoderm, and consecutive waves of EMT and MET occur in the generation of diverse cell types and tissues. EMT is pathologically reactivated in, and contributes to, the progression of fibrosis and cancer. In carcinomas, EMT has been associated with the generation of invasive cells and acquisition of cancer stem cell properties. EMT is initiated by the deconstruction of epithelial cell–cell junctions and apical–basal polarity, subsequently enabling the cells to establish a front–rear polarity, which is required for directional migration. Further changes in cell adhesion and membrane extrusions contribute to the increased cell motility following EMT. Integral in the EMT process is the reprogramming of gene expression, that is, the repression of an epithelial gene expression pattern and the activation of genes that contribute to EMT and the mesenchymal phenotype. EMT-associated gene reprogramming involves key transcription factors with central roles in driving this transdifferentiation process. Superimposed on the changes in gene expression are extensive and selective alterations in the splicing patterns of nascent transcripts, which are mediated by changes in splicing factor expression. In addition, an extensive network of microRNAs (miRNAs) represses the expression of EMT transcription factors and other targets; in some cases, miRNAs regulate EMT and MET through functional feedback mechanisms. Transforming growth factor-β (TGFβ) family proteins are potent inducers of EMT, partly through the SMAD-mediated activation of EMT transcription factor expression and the subsequent SMAD-mediated control of their transcription activities. TGFβ family proteins also activate complementary non-SMAD signalling pathways that contribute to the induction and progression of EMT. EMT is elaborated through the functional cooperation of signalling pathways that can be activated by diverse extracellular signals. These pathways converge at multiple levels, including at the level of gene reprogramming. Epithelial–mesenchymal transition (EMT) is integral to development and pathology. This switch in cell differentiation and behaviour requires key transcription factors, including SNAIL, zinc-finger E-box-binding (ZEB) and basic helix–loop–helix transcription factors, and is regulated by several signalling pathways, including those mediated by the transforming growth factor-β (TGFβ) family. The transdifferentiation of epithelial cells into motile mesenchymal cells, a process known as epithelial–mesenchymal transition (EMT), is integral in development, wound healing and stem cell behaviour, and contributes pathologically to fibrosis and cancer progression. This switch in cell differentiation and behaviour is mediated by key transcription factors, including SNAIL, zinc-finger E-box-binding (ZEB) and basic helix–loop–helix transcription factors, the functions of which are finely regulated at the transcriptional, translational and post-translational levels. The reprogramming of gene expression during EMT, as well as non-transcriptional changes, are initiated and controlled by signalling pathways that respond to extracellular cues. Among these, transforming growth factor-β (TGFβ) family signalling has a predominant role; however, the convergence of signalling pathways is essential for EMT.